PENGGUNAAN MEDIA SOSIAL DAN KEPEKAAN SOSIAL SISWA DI SMA N 12 PEKANBARU - Satialisa Satialisa; Tri Umari; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The development of technology is inevitable and even the development of social media. 39% of the largest results in the survey, social media users are young people aged 16-21 years, not to mention among students also follow its development. So this study entitled "The Use of Social Media and Social Sensitivity Students in SMA N 12 Pekanbaru". The purpose of research is to know the use of social media and know the social sensitivity of students who use social media. Sample study 178 people. Quantitative descriptive research method. The instrument used was a questionnaire. Data analysis technique percentage. The results show that many students access social media every day. Social media used Instagram, LINE and WhatApp. The duration of accessing social media is more than five hours per day, four hours per day and three hours per day. The condition of accessing social media is before bed, get together with friends, certain events and wake up. Social media used by students to display self-image is by dividing the writing about the feelings and things they do, get entertainment like looking at the history shared by friends. Student social sensitivity is high in awareness of social conditions and the ability to respond to social conditions such as knowing current issues, helping others and thinking about the safety of others. From the research results obtained many students who use social media categorized medium that has a high social sensitivity. Recommendation: To parents and teachers to pay attention to the use of children's social media, so that children can use social media wisely and also help children develop social sensitivity. To the next researcher, to be able to examine some other variables and with other methods such as experiments or correlations.Key Words: Social media, Social sensitivity